Population Dynamics of Acyrthosiphon pisum (Homoptera: Aphididae) and Its Natural Enemies on Pisum sativum (L.) - Kemal Ali (Pest Managment Journal of Ethiopia, 2023)
The seasonal abundance o f pea aphid, Acyrthosiphon pisum (Harris) was studied in field peas at Denbi and Kulumsa, Ethiopia from 1995 to 1997. Foliage samples form 50 randomly selected plants were taken in plots and farmers fields to estimate the aphid populations. Aphids first appeared in late July or early August, 40-60 days after crop emergence, but populations remained low throughout July. Populations increased in September in all years coinciding with flowering and podding growth phases, the period most sensitive to aphid damage. In general, aphid populations reached a peak in the latter half o f September and showed a sharp decline in October as plants senesced. The natural enemies o f aphids recorded were coccinellids (Cheilomenes lunata and C. sulphured), syrphids and braconid wasps (Aphidius spp.) natural enemy populations followed trend similar to that o f aphids, and the highest density was recorded in early September. The population o f predators was low at all locations with the highest record of 9 per 50 sampled plants. The parasitiods caused up to 42% mortality o f aphids at Kulumsa in 1995 indicating their importance as biological control agents. The appearance o f natural enemies was late and lagged behind the pest population which reached economic injury level.